Penguatan Kelembagaan dan Pengembangan Potensi Ekonomi Masyarakat melalui Pengelolaan Saluran Irigasi Menjadi Wisata Literasi pada Kelompok Budidaya Ikan (POKDAKAN) “Banyu Bening” Jajag Banyuwangi - Nurul Inayah; Nawal Ika Susanti; M. Rizkon Al Musafiri; Lely Ana Ferawati Ekaningsih (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
“Banyu Bening” fish village has the potential to become an alternative of literacy tourism and can be developed to increase the economic income for the local community, especially the porters. One of the obstacles faced was the conflict between management and the managerial from POKDAKAN which made the condition of “Banyu Bening” fish village was not optimal. Therefore, by fostering institutional strengthening in the “Banyu Bening” fish village, it is hoped that this potential can be used as an alternative for literacy tourism. This community service was based on Asset-Based Community Development (ABCD) approach and was implemented through training on the development of literacy culture based on local potential and conducting FGDs for institutional strengthening. The program has resulted in improved management of POKDAKAN and optimizing economic improvement through fish farming development in the irrigation water as well as media of education for litearcy tourism.